A translation control module coordinates germline stem cell differentiation with ribosome biogenesis during Drosophila oogenesis. - Martin, E.T.; Blatt, P.; Nguyen, E.; Lahr, R.; Selvam, S.; Yoon, H.A.M.; Pocchiari, T.; Emtenani, S.; Siekhaus, D.E.; Berman, A.; Fuchs, G.; Rangan, P. (Developmental Cell, 2022)
Ribosomal defects perturb stem cell differentiation, and this is the cause of ribosomopathies. How ribosome levels control stem cell differentiation is not fully known. Here, we discover that three DExD/H-box proteins govern ribosome biogenesis (RiBi) and Drosophila oogenesis. Loss of these DExD/H-box proteins, which we name Aramis, Athos, and Porthos, aberrantly stabilizes p53, arrests the cell cycle, and stalls germline stem cell (GSC) differentiation. Aramis controls cell-cycle progression by regulating translation of mRNAs that contain a terminal oligo pyrimidine (TOP) motif in their 5' UTRs. We find that TOP motifs confer sensitivity to ribosome levels that are mediated by La-related protein (Larp). One such TOP-containing mRNA codes for novel nucleolar protein 1 (Non1), a conserved p53 destabilizing protein. Upon a sufficient ribosome concentration, Non1 is expressed, and it promotes GSC cell-cycle progression via p53 degradation. Thus, a previously unappreciated TOP motif in Drosophila responds to reduced RiBi to co-regulate the translation of ribosomal proteins and a p53 repressor, coupling RiBi to GSC differentiation.